MEWASPADAI PROPAGANDA MELALUI KAJIAN SEJARAH (STUDI ATAS SISTEM PROPAGANDA JEPANG DI JAWA 1942-1945) - Yuliati, Dewi (HUMANIKA, 2012)
This article describes the Japanese propaganda system in Java during its occupation (1942-1945). Before its invasion in Java the Japanese had already prepared the propaganda system intensively. The goal of the propaganda was to mobilize the commitment of the Indonesian people to support the Japanese military government to become the winner in the Greater East Asia war against the Allies. The system of the Japanese propaganda in Java includes institutions, methods, packages of propaganda, and control systems. The most important package of the Japanese propaganda was art, especially poetry, prose, drama, and songs. Because of its entertaining values, the Indonesian people could easily absorbed the propaganda substances without awareness that they were indoctrinated. Keywords: Japanese propaganda, Japanese control system